CollaborativeGovernance in Zimbabwe’sUrban Local Authorities: Challenges and Considerations for Improved Service Delivery - Nyikadzino, Tawanda; Vyas-Doorgapersad, Shikha (Universitas PGRI Madiun, 2023)
Together with the influence of globalisation and sustainable development goals, urbanisation profoundly impacts the service delivery capacity of African subnational governments. Unfortunately, in the context of Zimbabwean local authorities, particularly urban councils, these amplified demands were not accompanied by increased capacity. Unsurprisingly, service delivery woes have become the norm. The question that arises is: Are urban local authorities in Zimbabwe, without the involvement and active participation of other stakeholders, able to confront and overcome service delivery challenges, and spearhead local development? In this article, the researchers present the impediments to collaborative governance in Zimbabwe’s urban councils and insights towards an enabling environment for collaborative governance. The researchers gathered evidence to substantiate this line of argument through qualitative desktopresearch.